Open Access

Traveling wave solutions of Zakharov–Kuznetsov-modified equal-width and Burger’s equations via \( {\text{exp}}( - \varphi \left( \eta \right)) \)-expansion method

  • Syed Tauseef Mohyud-Din1Email author,
  • Ayyaz Ali1 and
  • Muhammad Asad Iqbal1
Asia Pacific Journal on Computational Engineering20152:2

DOI: 10.1186/s40540-015-0014-y

Received: 1 June 2015

Accepted: 20 September 2015

Published: 7 October 2015

Abstract

In this article, a technique is proposed for obtaining better and accurate results for nonlinear PDEs. We constructed abundant exact solutions via exp\( ( - \varphi \left( \eta \right)) \)-expansion method for the Zakharov–Kuznetsov-modified equal-width (ZK-MEW) equation and the (2 + 1)-dimensional Burgers equation. The traveling wave solutions are found through the hyperbolic functions, the trigonometric functions and the rational functions. The specified idea is very pragmatic for PDEs, and could be extended to engineering problems.

Keywords

Exp\( ( - \varphi \left( \eta \right)) \)-expansion method Nonlinear evolution equation (ZK-MEW) equation Burger’s equation Solitary wave solutions

Background

Over the past few decades, researchers have shown keen interest in the solutions of nonlinear partial differential equations (PDEs).In the study of nonlinear physical phenomena, the investigation of solitary wave solutions [144] of nonlinear wave equations shows an important role. Scientific problems arise nonlinearly in numerous fields of mathematical physics, such as fluid mechanics, plasma physics, solid-state physics and geochemistry. Due to exact interpretation of nonlinear phenomena, these problems have gained much importance. However, in recent years, a variety of effective analytical methods has been developed to study soliton solutions of nonlinear equations, such as Backlund transformation method [1], tanh method [26], extended tanh method [712], pseudo-spectral method [13], trial function [14], sine–cosine method [15], Hirota method [16], exp function method [1725], \( (G^{'} /G) \)-expansion method [2630], homogeneous balance method [31, 32], F-expansion method [3335] and Jacobi elliptic function expansion method [3638]. Ma et al. [3944] established the complexiton solutions for Toda lattice equation. The theme of the method is that the exact solutions of nonlinear evolution equations can be articulated by exp\( ( - \varphi \left( \eta \right)) \), where \( \varphi \left( \eta \right) \) gratifies the ordinary differential equation (ODE):
$$ \left( {\varphi '\left( \eta \right)} \right) = { \exp }\left( { - \varphi \left( \eta \right)} \right) + \mu \,\, { \exp }\left( {\varphi \left( \eta \right)} \right) + \lambda $$
(1)
where \( \eta = x - Vt. \)

Explanation of exp\( ( - \varphi \left( \eta \right)) \)-expansion method

Now, the exp\( ( - \varphi \left( \eta \right)) \)-expansion method will be explained for constructing traveling wave solutions. Consider the general nonlinear partial differential equation for \( u\left( {x,t} \right) \) is given by,
$$ \phi \left( {u,u_{t} ,u_{x} ,u_{tt} ,u_{xx} ,u_{xxx} , \ldots } \right) = 0, $$
(2)
where \( u\left( \eta \right) = u\left( {x,t} \right), \) \( \phi \) is a polynomial of \( u \) and its derivatives. Solving (2), the following steps are as.
Step 1 We Combine the variables by \( \eta , \)
$$ u = u\left( \eta \right),\quad \eta = x - Vt, $$
(3)
where V is the speed of wave. Using Eqs. (3, 2) reduced to the following ODE for \( u = u\left( \eta \right) \)
$$ G\left( {u, u^{\prime}, u^{\prime\prime}, u^{\prime\prime\prime}, u^{\prime\prime\prime\prime}, \ldots } \right) = 0, $$
(4)
Step 2 The solution of Eq. (4) can be articulated as
$$ u\left( \eta \right) = \mathop \sum \limits_{n = 0}^{M} \,\, a_{n} \,\, \left( {{ \exp }\left( { - \varphi \left( \eta \right)} \right)} \right)^{\text{n}} , $$
(5)
where \( a_{n} 0 \le n \le M \) are constants such that \( a_{n} \ne 0 \) and \( \varphi \left( \eta \right) \) satisfies Eq. (1). Our solutions now depend on the parameters involved in (1).
Family 1: When \( \lambda^{2} - 4\mu > 0, \) we have
$$ \varphi \left( \eta \right) = { \ln }\left\{ {\frac{1}{2\mu }\left( { - \sqrt {\left( {\lambda^{2} - 4\mu } \right)} { \tanh }\left( {\frac{{\sqrt {\left( {\lambda^{2} - 4\mu } \right)} }}{2}(\eta + c_{1} )} \right) - \lambda } \right)} \right\}. $$
(6)
Family 2: When \( \lambda^{2} - 4\mu < 0, \) we have
$$ \varphi \left( \eta \right) = { \ln }\left\{ {\frac{1}{2\mu }\left( {\sqrt {\left( {\lambda^{2} - 4\mu } \right)} { \tan }\left( {\frac{{\sqrt {\left( {\lambda^{2} - 4\mu } \right)} }}{2}(\eta + c_{1} )} \right) - \lambda } \right)} \right\}. $$
(7)
Family 3: When \( \lambda^{2} - 4{\kern 1pt} {\kern 1pt} {\kern 1pt} {\kern 1pt} \mu > 0{\kern 1pt} {\kern 1pt} {\kern 1pt} {\kern 1pt} \mu = 0 \) and \( \lambda \ne 0, \)
$$ \varphi \left( \eta \right) = - { \ln }\left\{ {\frac{\lambda }{{\exp \left( {\lambda \left( {\eta + k} \right)} \right) - 1}}} \right\}. $$
(8)
Family 4: When \( \lambda^{2} - 4{\kern 1pt} {\kern 1pt} {\kern 1pt} \mu = 0,{\kern 1pt} {\kern 1pt} {\kern 1pt} \lambda \ne 0, \) and \( \mu \ne 0, \)
$$ \varphi \left( \eta \right) = { \ln }\left\{ {\frac{{2\left( {\lambda \left( {\eta + k} \right) + 2} \right)}}{{\left( {\lambda^{2} \left( {\eta + k} \right)} \right)}}} \right\}. $$
(9)
Family 5: When \( \lambda^{2} - 4{\kern 1pt} {\kern 1pt} {\kern 1pt} \mu = 0,{\kern 1pt} {\kern 1pt} {\kern 1pt} \lambda = 0, \) and \( \mu = 0, \)
$$ \varphi \left( \eta \right) = { \ln }(\eta + k) $$
(10)

Step 3 By considering the homogenous principal, in Eq. (4). Considering Eqs. (1, 4, 5), we have \( {\text{e}}^{M\varphi \left( \eta \right)} \). We get algebraic equations with \( a_{n} ,V,\lambda , \mu , \) after comparing the same powers of \( {\text{e}}^{\varphi \left( \eta \right)} \) to zero. We put the above values in Eq. (5) and with Eq. (1), we get some valuable traveling wave solutions of Eq. (2).

Solution procedure

Zakharov–Kuznetsov-modified equal-width equation

Consider the equation,
$$ u_{t} + \alpha \left( {u^{n} } \right)_{x} + \left( {\beta u_{xt} + \delta u_{yy} } \right)_{x} = 0, $$
(11)
where \( \alpha ,{\kern 1pt} \beta \) and \( \delta \) are some nonzero parameters. We use \( u = u\left( \eta \right),\eta = x + y - Vt, \) we can convert Eq. (11) into an ODE.
$$ - Vu^{\prime} - \beta Vu^{\prime\prime\prime} + \delta u^{\prime\prime\prime} + 2\alpha uu^{\prime} = 0, $$
(12)
where the dash denotes the derivative w. r. t. \( \eta \). Now integrating Eq. (12), we have,
$$ - Vu - \beta Vu^{\prime\prime} + \delta u^{\prime\prime} + \alpha u^{2} + C = 0, $$
(13)
Using homogenous principle, balancing \( u^{\prime\prime}\) and \( u^{2} \), we have
$$ \begin{aligned} 2M &= M + 2, \hfill \\ M &= 2. \hfill \\ \end{aligned} $$
The trial solution of Eq. (12) can be stated as,
$$ u\left( \eta \right) = a_{2} \left( {{ \exp }\left( { - \varphi \left( \eta \right)} \right)} \right)^{2} + a_{1} \left( {{ \exp }\left( { - \varphi \left( \eta \right)} \right)} \right) + a_{0} , $$
(14)
where \( a_{2} \ne 0,{\kern 1pt} {\kern 1pt} a_{1} \) and \( a_{0} \) are constants, while \( \lambda ,\mu \) are any constants.
Putting \( u, u^{\prime} , u^{\prime\prime} , u^{2} \) in Eq. (13) and comparing, we get,
$$ \begin{aligned} &\alpha a_{0}^{2} + \delta a_{1} \mu \lambda + C - 2\beta Va_{2} \mu^{2} - \beta Va_{1} \mu \lambda + 2\delta a_{2} \mu^{2} - Va_{0} = 0, \hfill \\ &2\alpha a_{0} a_{1} + \delta a_{1} \lambda^{2} + 2\delta a_{1} \mu + - 2\beta Va_{1} \mu - 6\beta V\mu \lambda - \beta Va_{1} \lambda^{2} + 6\delta a_{2} \mu \lambda - Va_{1} = 0, \hfill \\ &2\alpha a_{2} a_{1} + 10\delta a_{2} \lambda + 2\delta a_{1} + - 2\beta Va_{1} - 10\beta Va_{2} \lambda = 0, \hfill \\ &2\alpha a_{2} a_{1} + 10a_{2} \lambda + 2a_{1} + - 2\beta Va_{1} - 10\beta Va_{2} \lambda = 0, \hfill \\ &\alpha a_{2}^{2} + 6\delta a_{2} - 6\beta Va_{2} = 0, \hfill \\ \end{aligned} $$
(15)
By solving the algebraic equations, the required solution is given below.
$$ \left\{ {V = \frac{1}{6}\frac{{\alpha a_{2} + 6\delta }}{\beta }, {\kern 1pt} \lambda = 0, {\kern 1pt} a_{0} = a_{0} , a_{1} = 0, \mu = \frac{1}{2}\frac{1}{{\beta \alpha a_{2} }}\left(\sqrt 2 \sqrt {\beta \alpha \left( {6C\beta + 6\alpha \beta a_{0}^{2} - \alpha a_{0} a_{2} - 6a_{0} \delta } \right)} ,\right)} \}\right. $$
where \( \lambda \) and \( \mu \) are any constants.
Now putting the values in Eq. (14), we obtain
$$ u = a_{0} + a_{2} e^{ - 2\varphi \left( \eta \right)} , $$
(16)
where \( \eta = x - Vt. \) By putting (610) in (16), we obtain the solutions which are given below.
Case 1 When \( \lambda^{2} - 4\mu > 0 \) and \( \mu \ne 0, \) we have,
$$ u_{1} \left( \eta \right) = a_{0} + \frac{{4a_{2} \mu^{2} }}{{\left( { - \sqrt {\lambda^{2} - 4\mu } { \tanh }\left( {\frac{{\sqrt {\lambda^{2} - 4\mu } }}{2}\left( {\eta + c_{1} } \right)} \right) - \lambda } \right)^{2} }}, $$
where \( \eta = x - \frac{1}{6}\frac{{\alpha a_{2} + 6\delta }}{\beta }t \) and where \( c_{1} \) is any constant.
Case 2 When \( \lambda^{2} - 4\mu < 0 \) and \( \mu \ne 0, \) we have,
$$ u_{2} \left( \eta \right) = a_{0} + \frac{{4a_{2} \mu^{2} }}{{\left( {\sqrt { - \lambda^{2} + 4\mu } { \tan }\left( {\frac{{\sqrt { - \lambda^{2} + 4\mu } }}{2}\left( {\eta + c_{1} } \right)} \right) - \lambda } \right)^{2} }}, $$
where \( \eta = x - \frac{1}{6}\frac{{\alpha a_{2} + 6\delta }}{\beta }t \) and where \( c_{1} \) is any constant.
Case 3 When \( \mu = 0 \) and \( \lambda \ne 0, \) we have,
$$ u_{3} \left( \eta \right) = a_{0} + \frac{{a_{2} \lambda^{2} }}{{\left( {\exp \left( {\eta + c_{1} } \right)^{\lambda } - 1} \right)^{2} }}, $$
where \( \eta = x - \frac{1}{6}\frac{{\alpha a_{2} + 6\delta }}{\beta }t \) and where \( c_{1} \) is any constant.
Case 4 When \( \lambda^{2} - 4\mu = 0,{\kern 1pt} \lambda \ne 0, \) and \( \mu \ne 0, \) we obtain,
$$ u_{4} \left( \eta \right) = a_{0} + \frac{{a_{2} \left( {\eta + c_{1} } \right)^{2} \lambda^{4} }}{{\left( {2\left( {\eta + c_{1} } \right)^{\lambda } + 2} \right)^{2} }} , $$
where \( \eta = x - \frac{1}{6}\frac{{\alpha a_{2} + 6\delta }}{\beta }t \) and where \( c_{1} \) is any constant.

Case 5 When \( \lambda = 0, \) and \( \mu = 0, \) we have, \( u_{5} \left( \eta \right) = a_{0} + \frac{{a_{2} }}{{\left( {\eta + c_{1} } \right)^{2} }}, \) where \( \eta = x - \frac{1}{6}\frac{{\alpha a_{2} + 6\delta }}{\beta }t \) and where \( c_{1} \) is any constant.

Graphical demonstration

The graphs are given in Figs. 1, 2, 3, 4 and 5.
Fig. 1

Kink wave solution of \( u_{1} \) when \( a_{2} = 1, {\kern 1pt} {\kern 1pt} {\kern 1pt} a_{0} = 2,{\kern 1pt} {\kern 1pt} {\kern 1pt} y = 0, {\kern 1pt} {\kern 1pt} {\kern 1pt} \lambda = 3,{\kern 1pt} {\kern 1pt} {\kern 1pt} \mu = 2, {\kern 1pt} {\kern 1pt} {\kern 1pt} c_{1} = 1 \)

Fig. 2

Singular kink wave solution \( u_{2} \) when \( {\kern 1pt} a_{2} = 10, {\kern 1pt} {\kern 1pt} a_{0} = 8,{\kern 1pt} {\kern 1pt} {\kern 1pt} y = 0, {\kern 1pt} {\kern 1pt} {\kern 1pt} \lambda = 7,{\kern 1pt} {\kern 1pt} {\kern 1pt} {\kern 1pt} \mu = 5,{\kern 1pt} {\kern 1pt} {\kern 1pt} c_{1} = - 10 \)

Fig. 3

Singular kink wave solution \( u_{3} \) when \( a_{2} = 1, a_{0} = 2, y = 0, \lambda = 1, c_{1} = - 1 \)

Fig. 4

Singular kink wave solution \( u_{4} \) when \( {\kern 1pt} a_{2} = 3, a_{0} = 2, y = 0, \lambda = 5, \mu = 4, c_{1} = - 2 \)

Fig. 5

Singular kink wave solution \( u_{5} \) when \( a_{2} = 0.5, a_{0} = 0.2, y = 0, \lambda = 0.1, c_{1} = - 0.1 \)

(2 + 1)-dimensional Burger’s equation

Consider the equation,
$$ u_{t} - uu_{x} - u_{xx} - u_{yy} = 0, $$
(17)
where \( \alpha ,\beta \) and \( \delta \) are some nonzero parameters. We have, \( u = u\left( \eta \right) \), \( \eta = x + y - Vt, \) we can convert Eq. (17) into an ODE.
$$ - Vu^{\prime} - 2u^{\prime\prime} - uu^{\prime} = 0, $$
(18)
where dash denotes the derivative w. r. t.\( \eta.\)
Integrating Eq. (18), we have,
$$ - Vu - 2u^{\prime} - \frac{1}{2}u^{2} + C = 0, $$
(19)
Using homogenous principle, balancing the \( u' \) and \( u^{2} , \) we have, \( M = 1 \).
The trial solution of Eq. (18) can be stated as,
$$ u\left( \eta \right) = a_{1} \,\, \left( {{ \exp }\left( { - \varphi \left( \eta \right)} \right)} \right) + a_{0} , $$
(20)
where \( a_{1} \ne 0,{\kern 1pt} {\kern 1pt} {\kern 1pt} a_{0} \) is a constant, while \( \lambda ,\mu \) are any constants. By putting \( u, u^{\prime} , u^{\prime\prime} , u^{2} \) in Eq. (19) and comparing, we get
$$ \begin{aligned} &- \frac{1}{2}a_{0}^{2} + 2a_{1} \mu + C - Va_{0} = 0, \hfill \\ &- a_{0} a_{1} + 2a_{1} \lambda - Va_{1} = 0, \hfill \\ &- \frac{1}{2}a_{1}^{2} + 2a_{1} = 0, \hfill \\ \end{aligned} $$
(21)
By solving the algebraic equations, the required solution is given below.
$$ \left\{ {\begin{array}{*{20}c} {\lambda = \frac{1}{2}\sqrt {V^{2} + 2C + 16\mu } , a_{0} = - V + \sqrt {V^{2} + 2C + 16\mu } , \quad a_{1} = 4 ,} \\ {} \\ \end{array} } \right\}. $$
where \( \lambda \) and \( \mu \) are any constants. Now putting the values in Eq. (20), we obtain,
$$ u = - {\text{V}} + \sqrt {V^{2} + 2C + 16\mu } + 4e^{ - \varphi \left( \eta \right)} , $$
(22)
where \( \eta = x - Vt. \)

Now putting (610) in (22), we obtain the solutions as.

Case 1 When \( \lambda^{2} - 4\mu > 0 \) and \( \mu \ne 0, \) we have,
$$ u_{6} \left( \eta \right) = - 1 + \sqrt {1 + 2C + 16\mu } + \frac{8\mu }{{\left( { - \sqrt {\lambda^{2} - 4\mu } { \tanh }\left( {\frac{{\sqrt {\lambda^{2} - 4\mu } }}{2}\left( {\eta + c_{1} } \right)} \right) - \lambda } \right)}}, $$
where \( \eta = x - {\text{V}}t \) and where \( c_{1} \) is any constant.
Case 2 When \( \lambda^{2} - 4\mu < 0 \) and \( \mu \ne 0, \) we obtain,
$$ u_{7} \left( \eta \right) = = - 1 + \sqrt {1 + 2C + 16\mu } + \frac{8\mu }{{\left( { + \sqrt { - \lambda^{2} + 4\mu } { \tanh }\left( {\frac{{\sqrt { - \lambda^{2} + 4\mu } }}{2}\left( {\eta + c_{1} } \right)} \right) - \lambda } \right)}}, $$
where \( \eta = x - {\text{V}}t \) and where \( c_{1} \) is any constant.
Case 3 When \( \mu = 0 \) and \( \lambda \ne 0, \) we have,
$$ u_{8} \left( \eta \right) = = = - 1 + \sqrt {1 + 2C + 16\mu } + \frac{4\lambda }{{\left( {\left( {\eta + c_{1} } \right)^{\lambda } - 1} \right)}}, $$
where \( \eta = x - Vt \) and where \( c_{1} \) is any constant.
Case 4 When \( \lambda^{2} - 4\mu = 0, \lambda \ne 0, \) and \( \mu \ne 0, \) we obtain,
$$ u_{9} \left( \eta \right) = - 1 + \sqrt {1 + 2C + 16\mu } + \frac{{4\left( {\eta + c_{1} } \right)\lambda^{2} }}{{\left( {2\left( {\eta + c_{1} } \right)^{\lambda } + 2} \right)}}, $$
where \( \eta = x - Vt \) and where \( c_{1} \) is any constant.
Case 5 When \( \lambda = 0, \) and \( \mu = 0, \) we have,
$$ u_{10} \left( \eta \right) = - 1 + \sqrt {1 + 2C + 16\mu } + \frac{4}{{\left( {\eta + c_{1} } \right)}}, $$
where \( \eta = x - Vt \) and where \( c_{1} \) is any constant.

Graphical illustration

The graphs are given in Figs. 6, 7, 8, 9 and 10.
Fig. 6

Kink wave solution \( u_{6} \) when \( C = 1, a_{0} = 1, y = 0, \lambda = 3, \mu = 1, c_{1} = 1 \)

Fig. 7

Periodic solution \( u_{7} \left( \eta \right) \) when \( a_{2} = 2, C = 1, y = 0, \lambda = 1,\mu = 2, c_{1} = - 1 \)

Fig. 8

Singular kink wave solution \( u_{8} \) when \( \mu = 1, C = 1, y = 0, \lambda = 3, c_{1} = - 1 \)

Fig. 9

Singular kink wave solution \( u_{9} \) when \( a_{2} = 1, C = 1, y = 0, \lambda = 13,\mu = 1, c_{1} = - 1 \)

Fig. 10

Singular kink wave solution \( u_{10} \) when C = 15, y = 0, μ = 12, c 1 = −1

Conclusions

The exp\( ( - \varphi \left( \eta \right)) \)-expansion method has been successfully applied to find the exact solutions of (ZK-MEW) equation and the Burger’s equation. The attained results show that the proposed technique is effective and capable for solving nonlinear partial differential equations. In this study, some exact solitary wave solutions, mostly solitons and kink solutions, are obtained through the hyperbolic and rational functions. This study shows that the proposed method is quite proficient and practically well organized in finding exact solutions of other physical problems.

Declarations

Authors’ contributions

The work was carried out in cooperation among all the authors (STM-D, AA and MAI). All authors have a good involvement to plan the paper, and to execute the analysis of this research work together. All authors read and approved the final manuscript.

Compliance with ethical guidelines

Competing interests The authors declare that they have no competing interests.

Open AccessThis article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made.

Authors’ Affiliations

(1)
Department of Mathematics, Faculty of Sciences, HITEC University Taxila

References

  1. Ablowitz MJ, Clarkson PA (1991) Solitons, nonlinear evolution equations and inverse scattering. Cambridge University Press, New YorkView ArticleMATHGoogle Scholar
  2. Wazwaz AM (2004) The tanh-method for traveling wave solutions of nonlinear equations. Appl Math Comput 154:713–723MathSciNetView ArticleMATHGoogle Scholar
  3. Malfliet W, Hereman W (1996) The tanh method: exact solutions of nonlinear evolution and wave equations. Phys Scr 54:563–568MathSciNetView ArticleMATHGoogle Scholar
  4. Wazwaz AM (2007) The tanh-method for traveling wave solutions of nonlinear wave equations. Appl Math Comput 187:1131–1142MathSciNetView ArticleMATHGoogle Scholar
  5. Zayed EME, Abdel Rahman HM (2010) The tanh-function method using a generalized wave transformation for nonlinear equations. Int J Nonlinear Sci Numer Simul 11:595–601Google Scholar
  6. Wazwaz AM (2004) The tanh method for travelling wave solutions of nonlinear equations. Appl Math Comput 154:713–723MathSciNetView ArticleMATHGoogle Scholar
  7. Abdou MA (2007) The extended tanh method and its applications for solving nonlinear physical models. Appl Math Comput 190:988–996MathSciNetView ArticleMATHGoogle Scholar
  8. El-Wakil SA, Abdou MA (2007) New exact traveling wave solutions using modified extended tanh-function method. Chaos Solit Fract 31:840–852MathSciNetView ArticleMATHGoogle Scholar
  9. Zayed EME, AbdelRahman HM (2010) The extended tanh-method for finding traveling wave solutions of nonlinear PDEs. Nonlinear Sci Lett A 1(2):193–200Google Scholar
  10. Fan EG (2000) Extended tanh-function method and its applications to nonlinear equations. Phys Lett A 277:212–218MathSciNetView ArticleMATHGoogle Scholar
  11. Wazwaz AM (2008) The extended tanh-method for new compact and non-compact solutions for the KP–BBM and the ZK–BBM equations. Chaos Solit Fract 38:1505–1516MathSciNetView ArticleMATHGoogle Scholar
  12. Yaghobi Moghaddam M, Asgari A, Yazdani H (2009) Exact travelling wave solutions for the generalized nonlinear Schrödinger (GNLS) equation with a source by extended tanh–coth, sine–cosine and Exp-function methods. Appl Math Comput 210:422–435MathSciNetView ArticleMATHGoogle Scholar
  13. Rosenau P, Hyman JM (1993) Compactons: solitons with finite wavelengths. Phys Rev Lett 70:564–567View ArticleMATHGoogle Scholar
  14. Wazwaz AM (2003) An analytic study of compactons structures in a class of nonlinear dispersive equations. Math Comput Simul 63:35–44MathSciNetView ArticleMATHGoogle Scholar
  15. Wazwaz AM (2004) A sine-cosine method for handling nonlinear wave equations. Math Comput Model 40:499–508MathSciNetView ArticleMATHGoogle Scholar
  16. Hirota R (1971) Exact solutions of the Korteweg–de-Vries equation for multiple collisions of solitons. Phys Lett A 27:1192–1194View ArticleMATHGoogle Scholar
  17. Mohyud-Din ST (2009) Solution of nonlinear differential equations by exp-function method. World Appl Sci J 7:116–147Google Scholar
  18. Noor MA, Mohyud-Din ST, Waheed A (2008) Exp-function method for solving Kuramoto–Sivashinsky and Boussinesq equations. J Appl Math Comput. 29:1–13. doi:10.1007/s12190-008-0083-y MathSciNetView ArticleMATHGoogle Scholar
  19. Wu HX, He JH (2006) Exp-function method and its application to nonlinear equations. Chaos Solit Fract 30:700–708MathSciNetView ArticleMATHGoogle Scholar
  20. Mohyud-Din ST, Noor MA, Waheed A (2009) Exp-function method for generalized travelling solutions of good Boussinesq equations. J Appl Math Comput 30:439–445MathSciNetView ArticleMATHGoogle Scholar
  21. Abdou MA, Soliman AA, Basyony ST (2007) New application of exp-function method for improved Boussinesq equation. Phys Lett A 369:469–475View ArticleMATHGoogle Scholar
  22. Bekir A, Boz A (2008) Exact solutions for nonlinear evolution equation using Exp-function method. Phys Lett A 372:1619–1625MathSciNetView ArticleMATHGoogle Scholar
  23. Naher H, Abdullah FA, Akbar MA (2012) New travelling wave solutions of the higher dimensional nonlinear partial differential equation by the Exp-function method. J Appl Math 2012:14. doi:10.1155/2012/575387 MATHGoogle Scholar
  24. Zhu SD (2007) Exp-function method for the discrete m KdV lattice. Int J Nonlinear Sci Numer Simul 8:465–469Google Scholar
  25. Wu XH, He JH (2008) Exp-function method and its application to nonlinear equations. Chaos Solit Fract 38:903–910MathSciNetView ArticleMATHGoogle Scholar
  26. Wang M, Li X, Zhang J (2008) The (G′/G)-expansion method and travelling wave solutions of nonlinear evolution equations in mathematical physics. Phys Lett A 372:417–423MathSciNetView ArticleMATHGoogle Scholar
  27. Ebadi G, Biswas A (2011) The (G′/G)-expansion method and topological soliton solution of the K(m, n) equation. Commun Nonlinear Sci Numer Simulat 16:2377–2382MathSciNetView ArticleMATHGoogle Scholar
  28. Zayed EME, Gepreel KA (2009) The (G′/G)-expansion method for finding traveling wave solutions of nonlinear partial differential equations in mathematical physics. J Math Phys 50:013502–013512MathSciNetView ArticleGoogle Scholar
  29. Zayed EME, EL-Malky MAS (2011) The Extended (G′/G)-expansion method and its applications for solving the(3 + 1)-dimensional nonlinear evolution equations in mathematical physcis. Glob J Sci Front Res 11:13Google Scholar
  30. Ekici M, Duran D, Sonmezoglu A (2014) Constructing of exact solutions to the (2 + 1)-dimensional breaking soliton equations by the multiple (G′/G)-expansion method. J Adv Math Stud 7:27–44MathSciNetMATHGoogle Scholar
  31. Fan E, Zhang H (1998) A note on the homogeneous balance method. Phys Lett A 246:403–406MathSciNetView ArticleMATHGoogle Scholar
  32. Wang M (1995) Solitary wave solutions for variant Boussinesq equations. Phys Lett A 199:169–172MathSciNetView ArticleMATHGoogle Scholar
  33. Ebaid A, Aly EH (2012) Exact solutions for the transformed reduced Ostrovsky equation via the F-expansion method in terms of Weierstrass-elliptic and Jacobian-elliptic functions. Wave Motion 49:296–308MathSciNetView ArticleGoogle Scholar
  34. Filiz A, Ekici M, Sonmezoglu A (2014) F-expansion method and new exact solutions of the SchrÄodinger-KdV equation. Sci World J 2014:14View ArticleGoogle Scholar
  35. Abdou MA (2007) The extended F-expansion method and its applications for a class of nonlinear evolution equations. Chaos Solit Fract 31:95–104MathSciNetView ArticleMATHGoogle Scholar
  36. Dai CQ, Zhang JF (2006) Jacobian elliptic function method for nonlinear differential-difference equations. Chaos Solit Fract 27:1042–1047MathSciNetView ArticleMATHGoogle Scholar
  37. Liu D (2005) Jacobi elliptic function solutions for two variant Boussinesq equations. Chaos Solit Fract 24:1373–1385View ArticleMATHMathSciNetGoogle Scholar
  38. Chen Y, Wang Q (2005) Extended Jacobi elliptic function rational expansion method and abundant families of Jacobi elliptic functions solutions to (1 + 1)-dimensional dispersive long wave equation. Chaos Solit Fract 24:745–757View ArticleMATHGoogle Scholar
  39. Ma WX, Maruno K (2004) Complexiton solutions of the Toda lattice equation. Phys A 343:219–237MathSciNetView ArticleGoogle Scholar
  40. Ma WX, Zhou DT (1997) Explicit exact solution of a generalized KdV equation. Acta Math Scita 17:168–174Google Scholar
  41. Ma WX, You Y (2004) Solving the Korteweg—de Vries equation by its bilinear form: Wronskian solutions. Trans Am Math Soc 357:1753–1778MathSciNetView ArticleMATHGoogle Scholar
  42. Ma WX, You Y (2004) Rational solutions of the Toda lattice equation in Casoratian form. Chaos Solit Fract 22:395–406MathSciNetView ArticleMATHGoogle Scholar
  43. Ma WX, Fuchssteiner B (1996) Explicit and exact solutions of Kolmogorov–PetrovskII–Piskunov equation. Int J Nonlinear Mech 31(3):329–338MathSciNetView ArticleMATHGoogle Scholar
  44. Ma WX, Wu HY, He JS (2007) Partial differential equations possessing Frobenius integrable decompositions. Phys Lett A 364:29–32MathSciNetView ArticleMATHGoogle Scholar

Copyright

© Mohyud-Din et al. 2015